DAMPAK PELATIHAN TATA RIAS PENGANTIN TERHADAP KECAKAPAN WIRAUSAHA DI SKB BENGKULU SELATAN - Putri, Lidia Eka; Sofino, Sofino; Ulfasari, Nia (Comm-Edu (Community Education Journal), 2025)
This study aims to describe the extent of the impact of bridal makeup training on entrepreneurial skills at the Learning Activity Center (SKB) in South Bengkulu. This study is a mixed method with a convergent parallel design approach. The population in this study consists of participants in the bridal makeup training program at the SKB in South Bengkulu, with a sample size of 20 individuals. The sampling technique was conducted quantitatively using saturated sampling with 20 participants and qualitatively using purposive sampling with 5 participants. Instrument validation was performed by experts. Data collection techniques included questionnaires, observations, documentation, and interviews. Data analysis was conducted using descriptive statistics with percentage formulas, normality tests, and simple linear regression hypothesis tests. Data was collected through written questionnaires and interviews. The research results indicate that the influence of bridal makeup training on entrepreneurial skills is 85% based on the coefficient of determination test. This is supported by the results of bridal makeup training, which have an impact on participants' entrepreneurial skills, as evidenced by the interview results, where after participating in bridal makeup training, participants acquired makeup skills and started businesses independently or in groups in the field of makeup.